Efficacy of High-Voltage Pulsed Radiofrequency in Zoster-Associated Pain: A Meta-Analysis and Systematic Review - Yinghao Song; Ziheng Yu; Jingjing Guan; Haisheng Wu; Jinglang Zhang; Liu Qiaoling; Min Yuan; Xinzhi Cheng; Bingyu Ling (Anesthesiology Research and Practice)
Background. Zoster-associated pain (ZAP) is often refractory to conventional treatments and can seriously affect patients’ physical and mental health. High-voltage pulsed radio frequency (H-PRF) is a new method for treating ZAP with pulse voltages above 60 V or even up to 100 V. The purpose of this paper was to conduct a systematic review and meta-analysis to evaluate the efficacy of H-PRF in the management of ZAP. Methods. PubMed, Embase, and the Cochrane library were searched from their inception to June 2022 to identify controlled trials which evaluated the effectiveness of H-PRF compared with standard PRF and sham operations. The primary outcome was pain scores at different treatment times. The secondary outcomes included SF-36 scores, rescue analgesic dose, and side effects. Results. We reviewed 6 randomized controlled trials involving 428 patients. There was no significant difference between the H-PRF and standard PRF pain scores at 1 week after surgery and the sham operation group at 1 month. At 1, 3, and 6 months, the H-PRF group had better pain score than the standard PRF group, and at 3 months, the pain score was better than the sham operation group. The H-PRF group showed improvement in the SF-36 score, and there were no significant complications in the H-PRF group. Conclusions. H-PRF is an effective and safe treatment method that has better effects in relieving pain and improving the quality of life and physical and mental health. Although H-PRF provides pain relief rates comparable to those of the control group in the early stages, it remains the preferred and alternative treatment for relieving herpes zoster-related pain.